A rare isostructural series of 3d–4f cyanido-bridged heterometallic squares obtained by assembling [FeIII{HB(pz)3}(CN)3]− and LnIII ions: synthesis, X-ray structure and cryomagnetic study. Issue 41 (28th September 2021) - Alexandru, Maria-Gabriela; Visinescu, Diana; Cula, Beatrice; Shova, Sergiu; Rabelo, Renato; Moliner, Nicolás; Lloret, Francesc; Cano, Joan; Julve, Miguel
Abstract : A rare isostructural series of cyanido-bridged {Fe III Ln III }2 square-shaped heterobimetallic complexes were obtained, in which Tb III, Dy III and Er III derivatives show slow magnetization relaxation under zero and non-zero static fields. Abstract : A new series of cyanido-bridged {Fe III Ln III }2 neutral molecular squares of general formula [Fe{HB(pz)3 }(CN)(μ-CN)2 Ln(NO3 )2 (pyim)(Ph3 PO)]2 ·2CH3 CN [Ln = Ce (1 ), Pr (2 ), Nd (3 ), Gd (4 ), Tb (5 ), Dy (6 ) and Er (7 ); {HB(pz)3 } − = hydrotris(pyrazolyl)borate, pyim = 2-(1 H -imidazol-2-yl)pyridine and Ph3 PO = triphenylphosphine oxide] were obtained by reacting the low-spin [Fe{HB(pz)3 }(CN)3 ] − species with the preformed [Ln III (pyim)(NO3 )2 (pyim)(Ph3 PO)] + complex anions (generated in situ by mixing the nitrate salt of each Ln(iii ) ion with pyim and Ph3 PO molecules). Single-crystal X-ray diffraction studies show that 1–7 are isostructural compounds that crystallize in the triclinic P 1̄ space group. Their crystal structures consist of centrosymmetric cyanido-bridged {Fe III Ln III }2 molecular squares where two [Fe{HB(pz)3 }(CN)3 ] − units adopt bis-monodentate coordination modes towards two [Ln III (pyim)(NO3 )2 (pyim)(Ph3 PO)] + moieties. The cis -oriented convergent sites from both low-spin Fe III and Ln III fragments form a quasi square-shaped molecule in which the 3d and 4f ions alternatively occupy the corners of the square. Both Fe III ions show a distorted octahedral surrounding ( C 3v symmetry), whereas the Ln III ions exhibit a distorted muffin-like geometry ( C s symmetry) in 1–7 . The intramolecular Fe III ⋯Ln III distances across the two cyanido-bridges range from ca. 5.48/5.46 up to ca. 5.58/5.61 Å. The molecular squares in 1–7 are interlinked through hydrogen bonds, weak π⋯π stacking and very weak C–H⋯π type interactions into three-dimensional supramolecular networks. The analysis of the solid-state direct-current (dc) magnetic susceptibility data of 1–7 in the temperature range 1.9–300 K reveals the occurrence of weak intra- and intermolecular antiferromagnetic interactions. The small intramolecular antiferromagnetic couplings in 4 compare well with those previously reported for parent systems. Although the coexistence of the spin–orbit coupling (SOC) of the low-spin iron(iii ) and lanthanide(iii ) ions in the remaining compounds together with the ligand field effects mask the visualization and make difficult the evaluation of the possible magnetic interactions in them, we were able to do it through a SOC model applied on exact or effective Hamiltonians. Frequency-dependent alternating current magnetic susceptibility signals in the temperature range 2.0–9.0 K under zero and non-zero static fields were observed for 5–7 which indicate slow magnetic relaxation (SMM) behavior. The usual absence of χ ′′M maxima moved us to estimate their energy barriers through ln( χ ′′M / χ ′M ) vs. 1/ T plots, obtaining values from 25 to 40 cm −1 .